Electro‐Microfluidics: Biomimetic Meta‐Structured Electro‐Microfluidics (Adv. Funct. Mater. 51/2019). (17th December 2019) - Gao, Bingbing; Liao, Junlong; Guo, Maoze; Liu, Hong; He, Bingfang; Gu, Zhongze
Abstract : In article number 1906745, Bingfang He, Zhongze Gu, and co‐workers fabricate bio‐inspired meta‐structured membrane (MSMs) based electro‐microfluidics systems by constructing patterns on membranes with ordered micropillar and colloidal crystals. The flexible and free‐standing MSMs enable pumpless liquid flow, fluorescence enhancement, and offer a platform for building flexible electro‐microfluidics for skin chips and organ chips.